PENGEMBANGAN LKS SMA PADA MATERI BIOTEKNOLOGI KONVENSIONAL MELALUI EKSPERIMEN PEMBUATAN TEMPE MENGGUNAKAN BAHAN BAKU BIJI KARET - Setiawati, Lilis; mahadi, Imam; ', Darmawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Tempe is the food produced by simple fermentation technique by Rhizopus oligosporus. During tempeh on the market are made from only soybeans. While the last few years soybean production in Indonesia is decreasing and can not meet demand. Therefore, it is necessary to develop the manufacture of tempeh use other raw materials nutritional value is not lost either with tempeh from soy such as rubber seed (Havea bransiliensis) The purpose of this study was to determine the good treatment in the manufacture of tempeh and results of this study can be used for the development of LKS High School Biotechnology Conventional materials. This study consisted of two stages: the first stage, while the second phase of making tempe LKS development of research results. Research making tempe using the experimental method completely randomized design (CRD), which consists of 5 treatments and 3 ulangan.Hasil research it was concluded that in terms of content, protein content and levels of cyanide as well as organoleptic, treatment K4 is a good time in the making tempe. In the treatment K4memiliki protein content of 16.59%, cyanide levels at 0.0004% with perendama time of 24 hours and boiling for 120 minutes. The results of the research can be developed as a matter of Biotechnology Conventional LKS High School.Keywords: Keywords: tempe, rubber seed, conventional biotechnology, LKS